READABILITY IN TALK ACTIVE 2 TEXTBOOK FOR THE ELEVENTH GRADE SENIOR HIGH SCHOOL - Hera Fitra Lubis; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2017)
This research aimed to analyze and describe the readability of reading texts in atextbook entitled Talk Active 2 for the Eleventh Grade Senior High School. Thisresearch concerned on measuring six reading texts in the textbook which wereselected by using random sampling. The measurements used in this research wereFlesch Reading Ease Formula and Cloze Test. The test was distributed to the 40eleventh grade students at SMA Swasta Galih Agung. Furthermore, the writerused descriptive method. From the analysis by using Flesch Reading EaseFormula, it was found that 3 of 6 texts are readable for the eleventh gradestudents. The three texts are the third text Emperor Penguin (57.06), fifth textShould Parents Censor Their Children’s Reading Material? (63.59) and sixth textDewi Sartika (53.47). But, only the third text and sixth text are appropriate for theeleventh grade students because the scores are between 50 to 60 (Fairly Difficult)which estimated for 10th-12th grade. The average readability score of the six textsby using Flesch Reading Ease Formula is 51.35 (Fairly Difficult) which isappropriate for 10th-12th grade. Moreover, the results by using cloze test showedthat text 6 has score 78.80% (Independent Level) which is predicted to be quiteeasy and the students can read the text independently. Meanwhile, text 1 to 5 havescore between 40% to 60% (Instructional Level). The average score of six texts is59.7% (Instructional Level) which predicted to be appropriate difficulty and it canbe concluded that the reading texts are appropriate for the eleventh grade studentsand the students need teacher’s assistance to comprehend the texts.